Outcome Based Education Design in Elementary School Physical Education Lectures - Khairul Usman; Demmu Karo-karo; Wesly Silalahi; M. Irfan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
The aim of this research is to develop the concept of the Physical Education Course with the Outcome Based Education concept in the Elementary School Teacher Education Study Program. The Outcome Based Education concept is applied by utilizing technology as a lecture companion. The research method applied is Borg and Gall Design Research and Development. the effectiveness of the results can be explained that the implementation of Outcome Based Education in the Elementary School Physical Education course shows that it has an assessment of 94 which is in the Very Good category. The results of the Outcome-Based Education assessment have the highest score of the test scores carried out, namely in the limited test it gets a score of 66, in the main test it gets a score of 73, and in the operational test it gets a score of 93. The conclusion of the research shows that Elementary School Physical Education lectures can contribute as a rule an outcome-based education-based lecture development model through the application of the case method and team-based project lecture methods within the State University of Medan.